AB0115 Prophylactic and therapeutic activity of alkaline phosphatase in arthritic rats: single agent activity and in combination with methotrexate. (12th June 2018) - Chandrupatla, D.M.; Molthoff, C.F.; Ritsema, W.I.; Vos, R.; Elshof, E.; Matsuyama, T.; Low, P.S.; Musters, R.J.; Hammond, A.; Windhorst, A.D.; Lammertsma, A.A.; van der Laken, C.J.; et al.
Abstract : Background: Alkaline phosphatase (AP) is a gate-keeper of innate immune system responses by detoxifying (dephosphorylating) inflammation triggering moieties (ITMs) released from endogenous and external sources 1 and maintaining physiological barriers. Objectives: We examined whether AP's broad mechanism of action may serve as a safe therapeutic, either as single agent or combined with methotrexate (MTX), in rheumatoid arthritis (RA). Methods: A rat model for RA was used with repeated intra-articular methylated bovine serum albumin (mBSA) injections in one knee ("arthritic" knee), the contralateral knee serving as internal control. Recombinant human AP (200 µg, s.c.) was administered twice (spaced 4 days) before mBSA injections ( prophylactic setting) or after arthritis induction (4x, 2x/wk, therapeutic setting), or combined with MTX (0.3 mg/kg or 1 mg/kg, i.p.) in 4 rats/group. Plasma pharmacokinetics of AP in arthritic and healthy rats was monitored by colorimetric enzymatic assay. As an endpoint of AP/MTX treatment outcome, macrophage infiltration (marking arthritic conditions) in knee sections, liver and spleen was assessed by immunohistochemistry (ED1 and ED2-macrophage specific antibodies), immunofluoresence (macrophage marker; Folate Receptor-β, FRβ), and positron emission tomography (PET) scans and ex vivo tissue distribution with the macrophage tracer [ 18 F]fluoro-PEG-folate targeting FRβ. Results: After AP administration, both in healthy and arthritic rats, plasma AP levels increased over 1 hour to reach a maximum of 50%–70% above baseline. Increased plasma AP levels in healthy rats were retained for at least 4 hours, whilst in arthritic rats AP plasma levels steadily returned to baseline levels within this time frame, suggesting consumption of available AP by conjugating to its ITM substrates. Prophylactic and therapeutic schedules of AP treatment, either as single agent or in combination with MTX, were well tolerated. Both prophylactic and therapeutic AP markedly reduced synovial macrophage infiltration in arthritic knees (ED1; 3.5–4 fold, ED2; 3.5–6 fold), comparable with MTX treatment effects. AP/MTX combinations slightly improved on single agent effects. PET monitoring and ex-vivo tissue distribution studies corroborated the impact of AP, MTX and AP/MTX on reducing synovial macrophage infiltration. Beyond localised articular effects, AP also displayed systemic anti-inflammatory effects by a 2-fold reduction of ED1, ED2 and FRβ-positive macrophages in liver and spleen of arthritic rats. Conclusions: AP as single agent and combined with MTX elicits local and systemic anti-arthritic activity in arthritic rats and appears promising as a new therapeutic compound against arthritic conditions. Reference: [1] Pike AF, et al. Biochim Biophys Acta2013;1832:2044–56. Disclosure of Interest: D. Chandrupatla: None declared, C. Molthoff: None declared, W. Ritsema: None declared, R. Vos: None declared, E. Elshof: None declared, T. Matsuyama: None declared, P. Low: None declared, R. Musters: None declared, A. Hammond: None declared, A. Windhorst: None declared, A. Lammertsma: None declared, C. van der Laken: None declared, R. Brands Employee of: employee, G. Jansen: None declared